Influência do dicromato de potássio no comportamento do cimento aluminoso visando ao processo de S/E de resíduos com cromo - Ivanov, Raphael Coelli (2013)
The increasing amount of waste generated in several industries has been increasing over the years. Topics such as waste disposal and pollution risks of biological systems where these are deposited denote as main issues involved in advancing these sectors. Among the most widely used techniques of waste disposal process, Solidification / Stabilization (S / E) in the cement matrix are a prominent technology for immobilization of waste materials containing heavy metals. In this study, the aluminous cement (Fondu and Secar 51) and Portland cement (ARI) were used as binder materials aimed at immobilizing the potassium dichromate, which has as its main constituent Cr in the hexavalent state. The variations during hydration of cements before the addition of potassium dichromate were investigated using techniques of hydration heat monitoring and determination of the main phases formed and consumed. For this purpose, X-ray diffraction, scanning electron microscopy and thermal gravimetric analysis and differential thermal analysis were used. The results show that for this step adding of potassium dichromate resulted in reductions in the consumption of anhydrous phases, as well as the formation of the main hydrated phases for the three cements studied, being the addition of 2.5% of chromium (VI) responsible for the biggest decay. To investigate the efficiency of retention of chromium (hexavalent and total) and the evaluation of the structural integrity of the products formed, leaching techniques and mechanical strength were used. As results, the aluminous cement matrices showed the highest values of efficiency in retaining chrome, achieving more than 99%. However, the compressive strength parameter showed declines of up to 60% compared to the references folders with 0% chromium. As for the Portland, adding the chromium salt did not have a significantly influence in the compressive strength, however, the metal retention analysis indicates the ineffectiveness of this type of cement, since the concentrations above 0.5% chromium were leached to levels above the established norm.